2(1-x)=3(1+2x)+37

Simple and best practice solution for 2(1-x)=3(1+2x)+37 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(1-x)=3(1+2x)+37 equation:


Simplifying
2(1 + -1x) = 3(1 + 2x) + 37
(1 * 2 + -1x * 2) = 3(1 + 2x) + 37
(2 + -2x) = 3(1 + 2x) + 37
2 + -2x = (1 * 3 + 2x * 3) + 37
2 + -2x = (3 + 6x) + 37

Reorder the terms:
2 + -2x = 3 + 37 + 6x

Combine like terms: 3 + 37 = 40
2 + -2x = 40 + 6x

Solving
2 + -2x = 40 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
2 + -2x + -6x = 40 + 6x + -6x

Combine like terms: -2x + -6x = -8x
2 + -8x = 40 + 6x + -6x

Combine like terms: 6x + -6x = 0
2 + -8x = 40 + 0
2 + -8x = 40

Add '-2' to each side of the equation.
2 + -2 + -8x = 40 + -2

Combine like terms: 2 + -2 = 0
0 + -8x = 40 + -2
-8x = 40 + -2

Combine like terms: 40 + -2 = 38
-8x = 38

Divide each side by '-8'.
x = -4.75

Simplifying
x = -4.75

See similar equations:

| -20+x=18 | | 3x-4+1=-2x-5+5 | | n-14=23 | | 19+n=30 | | x-4=14x+9 | | 4/7(2c+9)=3/7 | | 8-3x=12+x | | 6(100-x)+3(100-y)=1500 | | 4x-2+x=-2x+2x | | 2/3x+6=-8 | | 3/5(h+10)=9 | | 4(k+3)+5k=75 | | x/12=16/24 | | x^3+x^2+4=0 | | 3/4x-3=18 | | 3/4-3=18 | | f(x)=28x^2+9x-4 | | 2/3(6t+12)=28 | | X+3/2x+6=0.5 | | x^2-3x+n=0 | | -0.1x^2+16x-100=0 | | 13x-3=62 | | 4x^3+5x^2-36x=45 | | x(x-2)+10=10 | | 0.1x^2+16x-100=0 | | 2t+a=19 | | 8x^2-8=6x | | X-6y=38 | | w^2-4w=32 | | 1/8=3r/4 | | c/-8=-14 | | 2.3=b/4 |

Equations solver categories